P132 Application of a hub-spoke model to severe asthma service delivery: outcomes from the birmingham regional centre. (December 2018) - Pillai, A; Marsh, J; Wilson, D; O'Hickey, S; Sahal, A; Szuszmann, A; Subramanian, D; Doherty, M; Message, S; Nagakumar, P; Taylor, C; Mansur, A
Abstract : Background: Severe asthma service specification (NHS England Service Specification No. 170002/S) advocates the development of regional severe asthma networks to improve patient outcomes and manage delivery of expensive treatments. The Birmingham Regional Severe Asthma Service (BRSAS) established a hub and spoke model including nine spokes. BRSAS orchestrates care within the region and conducts regular regional multidisciplinary meetings (MDT) to formulate management plans. Aim: To explore the clinical utility of the severe asthma network model of treatment delivery. Methods: All cases discussed at the BRSAS regional MDTs between July 2014 and March 2018 were reviewed. Cases were submitted online via a standardised severe/difficult to treat asthma proforma and data entered into a central database by an administrator. Questions for MDT included proposals for specialised treatment including biological therapy and bronchial thermoplasty (BT) and complex clinical issues managed at the respective sites were recorded. Results: A total of 23 MDTs were conducted over this study period that included 152 case submissions and (147 patients, mean age 46.6±14.1 years, 86 (57%) females, (mean 6.6 (6.39) per MDT). The main MDT questions were consideration for biological therapy (97/152 (63.8%), Mepolizumab 49 (50.5%), Omalizumab 30 (30.9%) or either 16 (16.5%), bronchial thermoplasty 5 (3.29%). Other questions were for confirmation of diagnosis (n=29), and use of macrolides (n=2), anti-fungal (n=2) and corticosteroid sparing agents (n=2). 6 (12.2%) cases were not approved for Mepolizumab and 7 (23.3%) for Omalizumab. Out of the 17 who were eligible for Mepolizumab and Omalizumab, 12 (70.6%) were approved for Omalizumab. 2/5 were accepted for BT. The most common reasons for non-approval of biological treatment were absence of eosinophilia (Mepolizumab), lack of allergy to a perennial allergen (Omalizumab) and requirement to treat coexisting comorbidities. Conclusion: Our regional severe asthma MDT service has enabled provision of effective use of expensive therapies and strengthened collaborations among our partners enabling delivery of more standardised care closer to the patient's home.